Postfeminist Trends in Contemporary Young Adult literature: The Reassessment of the Victim/Perpetrator Binary in Helen Cross’s My Summer of Love - Šnircová, Soňa (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The paper discusses a postmillennial trend in contemporary culture characterized by an “exhaustion of originary victimary experience” and the questioning of postmodern “victimary thinking”. It specifically focuses on postfeminists’ criticism of “victim feminism” and their attempts to question the firm ethical opposition of the female victim and the male perpetrator that is central to victim feminism discourse. After a brief theoretical discussion of postfeminist approaches to the victimary paradigm that dominates second wave feminism, the paper proceeds to explain how this paradigm influenced both twentieth-century criticism and production of female Bildung narratives. Finally, it presents Helen Cross’s coming-of-age novel My Summer of Love (2001) as an example of a new stage in the development of the genre marked by the author’s attempt to reassess the female victim/male perpetrator binary.
Keywords: postfeminism; victim; perpetrator; bildungsroman